Value chains for staple food crops in Uganda: Impediments and options for improvement - Namazzi, Juliet (International Food Policy Research Institute, 2008)
The market for food staples remains central to many agricultural-based economies because staple foods constitute such a major share of household food expenditures. Uganda is no different in this regard. Recognizing the importance of staple food markets both for general economic growth and broad poverty reduction and given the centrality of access to staple food for household welfare, the government of Uganda has targeted value addition for staple food crops as a priority area for agricultural development. In order to properly invest in value addition, one needs to look at the value chain for a staple food commodity as a whole and identify and alleviate constraints that hinder the development of a sustainable and growing market for it.